Citizenship under the light of founding treaties - Çataloluk, Gökçe (My University, 2004)
This research with the title 'Citizenship' under the Light of Founding Treaties' investigates the concept of European citizenship as was first cited and therefore constitutionalized in the Maastricht Treaty. The aim of the research is to examine the citizenship relation, which turns the individuals into authors of law, this regulation builds up between the European Union as a supranational entity and the nationals of its Member States and reveal the problem creating areas . The greater effect of the newly introduced European citizenship as a legal regulation was indeed in the political area of the Union. A part of the democracy deficit claim was constituted by struggles on citizenship which lead the German Federal Constitutional Court to rule: ' There is no European people therefore no European democracy'. I took the citizenship as an initiator of creating legal subjects in this research and questioned up to which point it satisfies this obligatory creation when it comes to the point of the political rights granted, the reflection of citizens' will in the decision making and the fixing of democratic deficit. The research starts with the necessity to define a supranational citizenship for a supranational entity, ends with the innovations introduced by the Draft Treaty Establishing a Constitution for Europe mentioning a line of legal problems. The outcome is that citizenship is taken as a mere legal regulation and not as an inclusive concept that the said regulation shall turn the individuals living in the Union into 'Citizens of the European Union'. There is a need of a more developed and extended understanding , having a stronger conceptual background as well as a true sense of legal belonging to create the feeling of being the authors of law for the citizens.

'Kurucu Anlaşmaların Işığı Altında Yurttaşlık' adını taşıyan bu çalışmada, Maastricht Anlaşması'nda ilk kez tanımlanan ve anayasal bir nitelik kazanan 'Avrupa Birliği Yurttaşlığı' çeşitli yönleriyle incelenmektedir. Çalışmanın amacı Birlik sınırları içerisinde yaşayan bireyleri, yurttaşlık kavramının tanımı gereği, hukukun özneleri haline getiren bu düzenlemenin ulus-üstü bir kurum olan Avrupa Birliği ile Üye Devlet vatandaşları arasında kurduğu yurttaşlık ilişkisini irdelemek, sorunlu noktalara temas etmektir. 1992 yılında imzalanan Maastricht Anlaşması'nın Birlik gündemine soktuğu Avrupa yurttaşlığı ilk bakışta salt bir hukuki düzenlemeyi andırsa da politik düzlemde de fazlasıyla yankı bulmuştur. Alman Federal Anayasa Mahkemesi'ni 'Bir Avrupa halkından söz edilemez' yargısında bulunmaya iten ve gündemden düşmeyen demokrasi eksikliği iddialarının bir parçasını da yurttaşlık oluşur. Bu çalışmada yurttaşlığın bireyleri hukuk öznesine dönüştürmesini bir gereklilik olarak alıp Avrupa Birliği bünyesinde yurttaşlara tanınan haklar, karar verme mekanizmalarında yurttaş iradesinin yansıması ve demokrasi eksiklerinin kapatılmasında yurttaşlık kavramının kullanılması noktalarında bu gerekliliğin ne derece ciddiye alındığını sorguladım. Araştırma ulus-üstü bir kurum için ulus- üstü bir yurttaşlık tanımlanmasının gerekliliğinden başlayıp taslak Birlik Anayasası'nda konu ile ilgili düzenlemelere kadar çeşitli konuları ele almıştır. Varılan netice, Avrupa Birliği yurttaşlığı ile ilgili hukuki düzenlemenin arka planında yurttaşların kendilerini hukuku yapıcıları olarak görmelerini sağlayacak denli kapsayıcı bir kavramsal altyapının bulunmadığını gösteriyor. Yurttaşların hukuk yapıcısı olarak görülmesi için daha geniş ve kavramsal olarak daha sağlam temellere oturtulmuş bir yurttaşlık tanımının yanı sıra aynı hukuka tabi bireylerin yurttaşlara dönüşmesini sağlayacak bir hukuki aidiyet duygusuna ihtiyaç vardır.
Keywords: Avrupa Birliği_Hukuk